#21 HPTLC standardization of Zandu haldi drops using curcumin as marker compound - HN, Aswatha Ram; Keerthana; Putta, Sanjay Kumar; Joseph, Khoeli Tlhokomelo; K, Aakarsh (Journal of Pharmaceutical Chemistry, 2022)
Zandu haldi drops is a one-of-a-kind recipe designed to improve immunity and overall health. It contains the goodness of saffron, cinnamon, cardamom, and black pepper, in addition to Haldi. Hence, the present work was aimed at the determination of haldi (turmeric) in Haldi drops by high-performance thin layer chromatography (HPTLC) with reference to the marker compound curcumin. The standard curve was prepared by weighing accurately 1 mg of curcumin in a volumetric flask, dissolved in methanol. Then make up the volume 10 mL with methanol to obtain a stock solution having 100 μg/mL concentration of curcumin. To prepare a working standard with a concentration of 10 g/mL, the standard stock solution of curcumin was diluted. The test sample solution of Zandu haldi drops was prepared by measuring 1 mL of the formulation in a 10 mL volumetric flask, dissolved in methanol. Then the volume was made up to 10 mL with diluent to obtain a stock solution having 100 µg/mL concentration. An accurately measured quantity is derived from this stock solution (1 mL) was dissolved in methanol in another 10 mL volumetric flask. Make up the volume to 10 mL with methanol to obtain a stock solution having 10 µg/mL concentration. The formulation extract and the marker compound were dissolved in methanol to make the concentration 10 µg/mL. The silica plates were preheated to remove the moisture and then the formulation extract and the standard samples were applied to it using the sample applicator. Then the samples were developed by the mobile phase [dichloromethane: methanol (99:1)]. After the development, the TLC plate was dried at room temperature. Then it was scanned in scanner3 at a wavelength of 421 nm. The amount of drug present was determined by comparing the sample’s peak area values to the standard’s, and the results were obtained. A curve of concentration Vs peak area of the standard was made and the concentration of curcumin present in the formulation solution used in this method was graphically extrapolated using the peak area of the formulation solution and was found to be 5.6 µg/mL. We conclude that the formulation Zandu haldi drops contains haldi as one of its ingredients and its presence was confirmed with reference to curcumin.